Antibiotic eye drops prescription patterns by orthokeratology practitioners in China and the development of antibiotic usage guidelines. Issue 4 (August 2021) - Chen, Zhi; Jiang, Jun; Xu, Jingjing; Yang, Xiao; Yang, Yin; Wang, Kai; Song, Hongxin; Yang, Bi; Cho, Pauline
Abstract: Purpose: To investigate antibiotic eye drops prescribing patterns of contact lens practitioners in Mainland China for orthokeratology (ortho-k) patients and to develop guidelines for their use. Methods: A questionnaire on their antibiotic prescribing habits was administered to eye care practitioners (ECP) involved in ortho-k lens fitting nationwide via an official online account. Multiple logistic regression models were used to assess the relationships between prescribing habits and demographics. Results: A total of 555 ECP completed the survey, of whom 50.5 % were optometrists (non-medical degree). About 30 % of the respondents routinely prescribed antibiotic eye drops for prophylactic use before and/or after commencement of ortho-k treatment. Forty one percent of the respondents dispensed antibiotics to patients for emergency use without giving written instructions, 48.5 % used antibiotic eye drops to wet fluorescein strips during ortho-k lens fitting, and 44.9 % considered treating corneal infiltrate(s) with antibiotics to be appropriate. A set of guidelines, including when to use antibiotic eye drops during ortho-k lens treatment and their proper use, stratified by different corneal conditions, was developed. Conclusions: Inappropriate use of antibiotic eye drops appeared to be common among ortho-k practitioners in Mainland China. Taking into account deficiencies and errors identified from the survey, a set of guidelines based on best practice was developed and can serve to provide advice for proper use of antibiotics in ortho-k practice.